2016
DOI: 10.1016/j.bbrep.2015.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Soluble form of the ST2 gene product exhibits growth promoting activity in NIH-3T3 cells

Abstract: The ST2 gene is induced in murine fibroblast cells at the start of cell proliferation. Although IL-33 has been identified as a ligand for one of the two major gene products of ST2 – namely, the transmembrane receptor form ST2L – prompting immunological research on inflammation, the roles of the ST2 gene products in cell proliferation remain to be elucidated.Using a cell proliferation assay system with NIH-3T3 cells, a normal murine fibroblast cell line, we found that treatment with recombinant ST2 caused an ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 28 publications
2
8
0
Order By: Relevance
“…On the other hand, we already reported that ST2L was dispensable for the cellular transformation [24] . Taking these observations together, it was suggested that ST2 more critically contributed to cellular transformation than ST2L, and this is well fit with our previous report [25] .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…On the other hand, we already reported that ST2L was dispensable for the cellular transformation [24] . Taking these observations together, it was suggested that ST2 more critically contributed to cellular transformation than ST2L, and this is well fit with our previous report [25] .…”
Section: Discussionsupporting
confidence: 91%
“…We also found that the knockdown of ST2 gene products slowed down cell proliferation [25] . To determine whether ST2 gene products might positively regulate cell cycle progression, we silenced the expression of ST2 gene products in NIH-3T3 cells using sh-RNA and examined its effects on cell cycle progression from G 0 to G 2 /M phase.…”
Section: Resultsmentioning
confidence: 65%
See 2 more Smart Citations
“…On the other hand, it was also reported that the IL-33/ST2L signaling axis exhibits an antitumor function [32,33], suggesting that the functional direction of ST2 gene products seems to depend on the environmental conditions such as the tumor cell type. Additionally, we reported recently the functional importance of ST2 for cell cycle progression provoked by serum stimulation [34], and our study suggested that ST2 seems to be involved in cell proliferation of not only tumor cells but also normal fibroblasts. These observations emphasized the importance of investigation of the mechanism by which the ST2 promoter is regulated.…”
Section: Discussionsupporting
confidence: 60%